THE INFLUENCE OF ASPECT RATIO OF REBAR-WIRE FIBER ON RHEOLOGICAL AND MECHANICAL PROPERTIES OF SELF CONSOLIDATING CONCRETE - INyoman Merdana; Fathmah Mahmud; Pathurrahman; Suparjo (Jurnal Infrastruktur, 2023)
It is often observed that compacting device is not applied optimally when faced with difficult placement situations and self-compacting concrete is as one of solution. The production of the concrete is carried out by optimizing aggregate size and proportion as well as certain amount of superplasticizer. In order to improve tensile strength of concrete, then local rebar wire fiber, widely known in Indonesia as Bendrat, can be involved to the fresh concrete, however workability of Self-compacting concrete will be reduced as the aspect ratio of rebar wire fiber increases. This research is intended to discover the effect of aspect ratio of local rebar wire fiber on the mechanical properties of Normal Strength Self compacting concrete. Concrete samples used in this study are 150x300mm concrete cylinder made according to EFNARC recommendation. The diameter of rebar-wire fiber is kept constant namely 0.7mm whereas the aspect ratio varies between 60-100. Compressive strength, Splitting tensile strength and Flexural strength of Self-compacting concrete is obtained by testing of concrete samples according to SNI 1974:2011, SNI 2491:2014 and SNI 4431:2011 respectively. The results showed that Rheological properties of fresh concrete and mechanical properties of self-compacting concrete are highly influenced by aspect ratio of rebar wire fiber. Rheological properties, such as Flowability, Passing ability and Segregation resistance decreases as the aspect ratio increases. Moreover, the research result indicate that Compressive strength of self-compacting concrete is insignificantly improved as the Aspect rasio increase. Optimum compressive strength is obtained from concrete specimens with aspect rasio of 70. On the other hand, the addition of rebar wire fiber on the fresh concrete significantly govern the properties of Tensile strength of self-compacting concrete with the optimum aspect rasio ranging from 70-80.